2017
DOI: 10.1371/journal.pone.0183808
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pneumonia in patients with gastroesophageal reflux disease: A population-based cohort study

Abstract: PurposeThe prevalence of gastroesophagel reflux disease (GERD) has steadily increased. However, the association between GERD itself and the risk of pneumonia remains unclear. This study aimed to investigate the association between GERD and long-term risk of pneumonia and to identify the major risk factors for pneumonia in GERD patients.MethodsUsing the Taiwan National Health Insurance Research Database, we identified patients who were newly diagnosed with GERD and treated with proton pump inhibitors (PPIs) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
1
28
0
2
Order By: Relevance
“…The patients with pneumonia were identified according to the International Classification of Diseases, Ninth Revision, Clinical Modification codes as previously described. 5 , 17 For patients with more than one episode of pneumonia, only the first episode was included. A severe exacerbation was defined as a COPD-related hospitalization or emergency department visit.…”
Section: Methodsmentioning
confidence: 99%
“…The patients with pneumonia were identified according to the International Classification of Diseases, Ninth Revision, Clinical Modification codes as previously described. 5 , 17 For patients with more than one episode of pneumonia, only the first episode was included. A severe exacerbation was defined as a COPD-related hospitalization or emergency department visit.…”
Section: Methodsmentioning
confidence: 99%
“…Another study demonstrated that cardiovascular function declined in elderly patients with heart disease, which would affect the mucociliary clearance functions that trap and remove particulates and pathogens from the airways, leading to an increased risk of incident pneumonia [ 35 ]. Furthermore, a population-based cohort study indicated that GERD is associated with a long-term risk of pneumonia, especially in GERD with proton pump inhibitors (PPIs) for a longer treatment than four months [ 36 ]. There is a relationship between gastric acid suppressants and an increased risk of pneumonia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…DM in both cases and controls was assessed on the basis of at least three outpatient claims or at least one inpatient claim of ICD-9 Code 250.xx. Other medical conditions potentially associated with acute epiglottitis, including asthma (ICD-9-CM code: 493.xx), chronic liver disease and cirrhosis (ICD-9-CM code: 571.xx), coronary artery disease (ICD-9-CM codes: 410–414), hypertension (ICD-9-CM codes: 401–405), and pneumonia and influenza (ICD-9-CM codes: 480–488), upper digestive tract cancer (ICD-9-CM codes: 141–151), autoimmune diseases (ICD-9-CM codes: 714.0, 720, 720.0, 710.0, 370.33, 710.2, 710.1), chronic obstructive pulmonary disease (COPD, ICD-9-CM codes: 490–496), alcohol dependence and abuse (ICD-9-CM codes: 303, 303.xx, 305.0, 305.0x), corrosive injury of upper digestive tract (ICD-9-CM codes: 947.0–947.3), and gastroesophageal reflux disease (GERD, ICD-9-CM codes: 530.11, 530.81,530.85) were also assessed from the claims data[ 11 , 13 , 15 , 26 , 27 , 33 37 ]. We included these comorbidities if they occurred either in the inpatient setting or in more than three ambulatory care claims.…”
Section: Methodsmentioning
confidence: 99%